2016
DOI: 10.1002/adma.201505129
|View full text |Cite
|
Sign up to set email alerts
|

High‐Precision Twist‐Controlled Bilayer and Trilayer Graphene

Abstract: Twist-controlled bilayer graphene (tBLG) and double-twisted trilayer graphene (DTTG) with high precision are fabricated and their controllable optoelectronic properties are investigated for the first time. The successful fabrication of tBLG and DTTG with designated θ provides an attractive starting point for systematic studies of interlayer coupling in misoriented few-layer graphene systems with well-defined geometry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
100
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(105 citation statements)
references
References 34 publications
2
100
0
Order By: Relevance
“…Recently, the TBG with a precise rotation angle of 30 • was experimentally realized and its spectrum measured in epitaxially grown samples on top of SiC surface 16 . In addition, similar TBGs have been realized on top of Ni surface 17,18 and also by a transfer method 19 . Moreover, another 30 • -rotated stack of atomic layers have also been realized in graphene on top of BN layer 20 as well as MoSe 2 bilayer system 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the TBG with a precise rotation angle of 30 • was experimentally realized and its spectrum measured in epitaxially grown samples on top of SiC surface 16 . In addition, similar TBGs have been realized on top of Ni surface 17,18 and also by a transfer method 19 . Moreover, another 30 • -rotated stack of atomic layers have also been realized in graphene on top of BN layer 20 as well as MoSe 2 bilayer system 21 .…”
Section: Introductionmentioning
confidence: 99%
“…The nonlinear ionizations are almost independent on the initial defects of the target materials. Hence, femtosecond laser ablation is deterministic and reproducible 7 , and almost any material can be machined using a femtosecond laser, including metals 8 , 9 , 10 , semiconductors 11 , 12 , dielectrics 13 , 14 , polymers 15 , two-dimensional materials 16 , 17 , 18 , 19 , 20 , ultrahard materials 21 and biological tissues 22 , 23 . In addition, ionization mechanism can be adjusted by changing femtosecond laser energy and its temporal/spatial distribution to control laser-material interactions 24 .…”
Section: Introductionmentioning
confidence: 99%
“…This assumption was not unreasonable because AB stacking (interplanar spacing 3.35 Å) is the minimum energy configuration for planar graphene layers and the less stable AA stacking (interplanar spacing 3.53 Å) is not present in pure crystalline graphite2. With the progress in fabricating mono- and multilayer graphene3, unique Moiré patterns45678 are revealed arising from the atomic-resolution transmission electron microscopy (TEM) morphology with rotating angles between graphene planes (i.e., disorderly stacked), and are proved as the signature of disordered graphite. Recently, we have shown that AA’ stacking of graphene planes (where each graphene plane is shifted by 1/2 hexagon from zigzag AA stacking or by 1/4 hexagon from armchair AB stacking) exists, and may be the structure of multi-wall carbon nanotubes (MWNTs) (i.e., helically grown AA’ graphite)910.…”
mentioning
confidence: 99%